Potensi Eco-Enzyme Berbasis Limbah Kulit Buah sebagai Agen Biologis terhadap Karakteristik Fisikokimia Larutan Zat Warna Tekstil Komersil - Rahma Joni; Yelmiza; Gisha Pasha Mongan; Siti Fauziah; Nova Rosita Pakpahan (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2026)
Fruit peel waste is an abundant organic waste that can be utilized as a raw material for eco-enzyme production through fermentation. Eco-enzymes contain various fermentation-derived metabolites with the potential to function as environmentally friendly biological agents for wastewater treatment. This study aimed to evaluate the physicochemical characteristics of eco-enzymes produced from pineapple, orange, and papaya peels and to investigate their effects on the physicochemical characteristics of commercial textile dye solutions. Eco-enzymes were synthesized using a fruit peel, brown sugar, and water ratio of 3:1:10 (w/v) and fermented for 30 days. The eco-enzymes were characterized by measuring Total Dissolved Solids (TDS), pH, and Electrical Conductivity (EC) before and after fermentation. Subsequently, 50 mL of each eco-enzyme was added to 100 mL of commercial textile dye solution, and the mixtures were monitored for 72 hours. The results showed that fermentation reduced the pH of all eco-enzymes from 4.00 to 2.67 for pineapple peel, from 6.83 to 3.54 for orange peel, and from 5.29 to 2.82 for papaya peel. Variations in TDS and EC values indicated that the type of fruit peel influenced the physicochemical properties of the resulting eco-enzyme. Application of the eco-enzymes to commercial textile dye solutions reduced TDS values in all treatments. Orange peel eco-enzyme exhibited the highest TDS reduction efficiency, reaching 50.46% after 72 hours, followed by pineapple peel (43.39%) and papaya peel (41.62%). These findings indicate that fruit peel-derived eco-enzymes have promising potential as environmentally friendly biological agents for modifying the physicochemical characteristics of commercial textile dye solutions.